Towards a Comprehensive Framework of Mediation Success: EU Mediation in the Belgrade–Pristina Dialogue - Plänitz, Erik (Journal of Regional Security, 2018)
The European Union has gained increasing importance in international mediation over the last decade. Driven by the powerful role assigned to the High Representative and the European External Action Service by the Lisbon treaty, the EU has been facilitating high-level talks between Belgrade and Pristina over their relationship since 2011. Although the signing of the Brussels Agreement in 2013 was a breakthrough, developments in north Kosovo suggest that the process might have significant shortcomings. This paper’s guiding research question of how to assess mediation success addresses the existing gap between external and internal perspectives. It introduces a comprehensive analytical framework to assess mediation success that combines several previously suggested ideas into a single framework. The question of how to measure successful mediation contributes not only to theory development but targets the interface between science and policymaking. The framework, as applied to the EU mediation ef- forts in the Belgrade–Pristina dialogue, has unveiled the in conclusive character of the process. Whilst being a success for the European Union, this paper argues a deficit in local legitimacy exists. Increasing levels of internal violence in Kosovo hint that it failed to fully address the root causes of the dispute.